Early Gelatinase Activity Is Not a Determinant of Long-Term Recovery after Traumatic Brain Injury in the Immature Mouse. - Bridgette D Semple; Linda J Noble-Haeusslein; Major Gooyit; Kayleen G Tercovich; Zhihong Peng; Trung T Nguyen; Valerie A Schroeder; Mark A Suckow; Mayland Chang; Jacob Raber; Alpa Trivedi (PLoS ONE, 2015)
The gelatinases, matrix metalloproteinases (MMP)-2 and MMP-9, are thought to be key mediators of secondary damage in adult animal models of brain injury. Moreover, an acute increase in these proteases in plasma and brain extracellular fluid of adult patients with moderate-to-severe traumatic brain injuries (TBIs) is associated with poorer clinical outcomes and mortality. Nonetheless, their involvement after TBI in the pediatric brain remains understudied. Using a murine model of TBI at postnatal day 21 (p21), approximating a toddler-aged child, we saw upregulation of active and pro-MMP-9 and MMP-2 by gelatin zymography at 48 h post-injury. We therefore investigated the role of gelatinases on long-term structural and behavioral outcomes after injury after acute inhibition with a selective gelatinase inhibitor, p-OH SB-3CT. After systemic administration, p-OH SB-3CT crossed the blood-brain barrier at therapeutically-relevant concentrations. TBI at p21 induced hyperactivity, deficits in spatial learning and memory, and reduced sociability when mice were assessed at adulthood, alongside pronounced tissue loss in key neuroanatomical regions. Acute and short-term post-injury treatment with p-OH SB-3CT did not ameliorate these long-term behavioral, cognitive, or neuropathological deficits as compared to vehicle-treated controls, suggesting that these deficits were independent of MMP-9 and MMP-2 upregulation. These findings emphasize the vulnerability of the immature brain to the consequences of traumatic injuries. However, early upregulation of gelatinases do not appear to be key determinants of long-term recovery after an early-life injury.